2012
DOI: 10.1080/02640414.2012.712711
|View full text |Cite
|
Sign up to set email alerts
|

Methods of monitoring the training and match load and their relationship to changes in fitness in professional youth soccer players

Abstract: Previous studies examining methods of monitoring the training and match load in soccer players have simply compared those methods to each other, not to changes in fitness. Training and match load measures from nine professional youth soccer players were collected for a period of six weeks. A lactate threshold test was conducted before and after this period. Mean weekly training and match load as determined by session-RPE, Banister's TRIMP, Team TRIMP and individualised TRIMP (iTRIMP) were correlated with each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
157
4
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(202 citation statements)
references
References 25 publications
13
157
4
8
Order By: Relevance
“…These results are in accordance with those of Gabbett et al (2005) and Gorostiaga et al (2006) which showed no change in the running test over an entire TS season. However, Akubat et al (2012) revealed that the weekly TL is positively correlated with an increase in fitness performance especially for aerobic effort. Nevertheless, YYRT2 is a test to evaluate the capacity of an individual to perform repeated intense exercise which requires aerobic and high anaerobic systems contribution (Bangsbo et al, 2008).…”
Section: Running Performance Testmentioning
confidence: 99%
“…These results are in accordance with those of Gabbett et al (2005) and Gorostiaga et al (2006) which showed no change in the running test over an entire TS season. However, Akubat et al (2012) revealed that the weekly TL is positively correlated with an increase in fitness performance especially for aerobic effort. Nevertheless, YYRT2 is a test to evaluate the capacity of an individual to perform repeated intense exercise which requires aerobic and high anaerobic systems contribution (Bangsbo et al, 2008).…”
Section: Running Performance Testmentioning
confidence: 99%
“…15 However, an approach that demonstrates the dose-response relationship between TL and fitness rather than the correlation between TL methods has been advocated. 10,16 While HR-based methods have been used descriptively in Rugby 2,13 , the fully individualised iTRIMP method which has shown preferential dose-response relationship with fitness in other sports 9,10,[16][17][18] has not been examined in Rugby. However, one study that evaluated Additionally, the use of MEMS has advanced the area of monitoring external physical performance beyond distance and speeds to include tri-axial accelerometer based derivatives of external TL.…”
Section: Introductionmentioning
confidence: 99%
“…8 TL measures that demonstrate a strong dose-response relationship will provide coaches with a greater understanding of how players may respond to a given training stimulus. 9,10 These studies allow coaches/sports scientists to evaluate which load measures would be useful when looking at a particular training outcome. TL measures are often used to help manipulate the training dose, however if these TL measures fail to inform a strong enough dose-response relationship the manipulation of training using such measures may not result in expected training outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Esse método vem sendo amplamente utilizado em estudos com diferentes modalidades esportivas, incluindo, por exemplo, o futebol (AKUBAT et al, 2012), rugby (LOVELL et al, 2013), basquetebol (MOREIRA et al, 2012aSCANLAN et al, 2014), voleibol (RODRÍGUEZ-MARROYO, 2014), futebol australiano (MOREIRA et al, 2015;SCOTT et al, 2012), natação (PSYCHARAKIS, 2011;WALLACE;SLATTERY;COUTTS, 2009), judô (VIVEIROS et al, 2011, tênis (GOMES et al, 2013), teamgym (MINGANTI et al, 2010), entre outros. A validade do método da PSE da sessão, para avaliar a carga de treinamento em diferentes tipos de treinamento (treinamento com pesos, treinamentos intervalados de alta intensidade, treinamento pliométrico, etc), também tem sido frequentemente reportada (FOSTER et al, 1995(FOSTER et al, , 2001HAMPSON et al, 2004;IMPELLIZZERI et al, 2004).…”
Section: Introductionunclassified